2002
DOI: 10.1093/ndt/17.11.1993
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial expression of alpha-SMA: an early marker of chronic renal allograft dysfunction

Abstract: This study suggests that alpha-SMA evaluation in time-zero biopsies, especially the combination of alpha-SMA expression and interstitial fibrosis, can strongly predict chronic renal allograft dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 21 publications
0
58
0
1
Order By: Relevance
“…Indeed, kidneys preserved in IGL-1 solution presented a degree of fibrosis similar to that of control kidneys while kidneys preserved in K-UW solution showed early appearance of fibrosis, which is specific for pig models [16]. Interstitial expression of alpha-SMA is considered an early marker of chronic renal allograft dysfunction and its evaluation in timezero biopsies can predict this event [24]. IGL-1 solution was found to be able to significantly limit the fibrosis, which is considered to be the lesion leading to chronic renal injury and progressive loss of renal function [25].…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, kidneys preserved in IGL-1 solution presented a degree of fibrosis similar to that of control kidneys while kidneys preserved in K-UW solution showed early appearance of fibrosis, which is specific for pig models [16]. Interstitial expression of alpha-SMA is considered an early marker of chronic renal allograft dysfunction and its evaluation in timezero biopsies can predict this event [24]. IGL-1 solution was found to be able to significantly limit the fibrosis, which is considered to be the lesion leading to chronic renal injury and progressive loss of renal function [25].…”
Section: Discussionmentioning
confidence: 96%
“…However, very little is known about the role of interstitial myofibroblast in the pathogenesis and progression of renal allograft fibrosis. Badid et al (33) suggested that interstitial ␣-SMA expression in pretransplant biopsies can strongly predict chronic renal allograft dysfunction. Recently, the presence of ␣-SMA-expressing interstitial myofibroblast in the development of chronic allograft nephropathy was suggested by Djamali et al (34) in an experimental model of chronic allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Furthermore, early myofibroblast infiltration predicts chronic renal allograft dysfunction in renal transplant recipients. 42 Additional studies to determine whether the degree of myofibroblast infiltration in the bronchial tissue correlates with clinical course of the disease would be useful in making clinical predictions. Our studies used two different murine models of BO to evaluate the role of IL-13 in the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%